Adjournments during TV watching: A closer look into the organisation of continuing states of incipient talk. (April 2016) - Ergül, Hatice
This article examines how participants collaboratively achieve projection of adjournments in TV audience interaction in Turkish. Adjournments are lapses in continuing states of incipient talk (CSIT) when the participants are not just talking but engaged in another activity. Adjournments during CSIT are neither attributable silences nor are they treated as accountable by the participants. Adopting the ethnomethodological tool of conversation analysis, the article reveals two types of episodes of talk in TV audience interaction: (1) adjacency pairs and (2) extended sequences. In adjacency pairs, an adjournment is projected through absence of mutual gaze and providing minimal agreements. In extended sequences, however, gaze aversion and demonstrable establishment of mutual alignment (e.g. using proverbial expression) are employed by the participants to hold the transition relevance place and project adjournments.